The role of Mycobacterium tuberculosis acetyltransferase and protein acetylation modifications in tuberculosis - Huang, Yinxia; Zhu, Chuanzhi; Pan, Liping; Zhang, Zongde (Frontiers in Cellular and Infection Microbiology, 2023)
Tuberculosis (TB) is a widespread infectious disease caused by Mycobacterium tuberculosis (M. tb), which has been a significant burden for a long time. Post-translational modifications (PTMs) are essential for protein function in both eukaryotic and prokaryotic cells. This review focuses on the contribution of protein acetylation to the function of M. tb and its infected macrophages. The acetylation of M. tb proteins plays a critical role in virulence, drug resistance, regulation of metabolism, and host anti-TB immune response. Similarly, the PTMs of host proteins induced by M. tb are crucial for the development, treatment, and prevention of diseases. Host protein acetylation induced by M. tb is significant in regulating host immunity against TB, which substantially affects the disease’s development. The review summarizes the functions and mechanisms of M. tb acetyltransferase in virulence and drug resistance. It also discusses the role and mechanism of M. tb in regulating host protein acetylation and immune response regulation. Furthermore, the current scenario of isoniazid usage in M. tb therapy treatment is examined. Overall, this review provides valuable information that can serve as a preliminary basis for studying pathogenic research, developing new drugs, exploring in-depth drug resistance mechanisms, and providing precise treatment for TB.